Nud1p, the yeast homolog of Centriolin, regulates spindle pole body inheritance in meiosis - Gordon, Oren; Taxis, Christof; Keller, Philipp J.; Benjak, Aleksander; Stelzer, Ernst H. K.; Knop, Michael (The EMBO journal, 2006)
Nud1p, a protein homologous to the mammalian centrosome and midbody component Centriolin, is a component of the budding yeast spindle pole body (SPB), with roles in anchorage of microtubules and regulation of the mitotic exit network during vegetative growth. Here we analyze the function of Nud1p during yeast meiosis. We find that a nud1‐2 temperature‐sensitive mutant has two meiosis‐related defects that reflect genetically distinct functions of Nud1p. First, the mutation affects spore formation due to its late function during spore maturation. Second, and most important, the mutant loses its ability to distinguish between the ages of the four spindle pole bodies, which normally determine which SPB would be preferentially included in the mature spores. This affects the regulation of genome inheritance in starved meiotic cells and leads to the formation of random dyads instead of non‐sister dyads under these conditions. Both functions of Nud1p are connected to the ability of Spc72p to bind to the outer plaque and half‐bridge (via Kar1p) of the SPB.